2007
DOI: 10.1016/j.vaccine.2007.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Spray drying of an attenuated live Newcastle disease vaccine virus intended for respiratory mass vaccination of poultry

Abstract: A powder vaccine intended for aerosol vaccination of poultry was formulated by spray drying a live attenuated Newcastle disease virus with potential stabilizers (mannitol, trehalose, polyvinylpyrrollidone (PVP), bovine serum albumin (BSA)). Thermodynamic properties, water sorption, particle size distribution, nebulization properties, density and morphology of the powders were evaluated and the virus survival during spray drying and storage was determined by incubation in embryonated eggs and subsequent haemagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 40 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…Other vaccination methods should be investigated, e.g., the dry aerosolization of vaccine virus (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Other vaccination methods should be investigated, e.g., the dry aerosolization of vaccine virus (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the trehalose-stabilized vaccine was maintained above 90% following 35 weeks storage at 45 • C, whereas the control vaccine (without trehalose) demonstrated less than 5% activity following 2.5 weeks of storage at the same temperature. Furthermore, analysis of aluminum hydroxide sedimentation revealed that trehalose-stabilized vaccine maintained 90% of the values of the fresh suspension control, whereas those stabilized in sucrose demonstrated only 50%, following 4 weeks of storage at 45 • C. Trehalose was also utilized to stabilize 17D Yellow Fever virus, 174 Newcastle disease virus, 175 and Rinderpest and Peste des Petits ruminants viruses. 176 All of the viruses were dried by different techniques, including freeze drying, spray drying, and foam drying; however, they all demonstrated the efficacy of trehalose in conferring stability to a wide variety of stresses.…”
Section: Virusesmentioning
confidence: 99%
“…It has been suggested (Huyge et al, 2012) that the ideal powder vaccine should meet the following requirements: (1) show no or only limited virus loss during production and storage; (2) be monodisperse; (3) consist of particles with a size that will enable exclusive targeting of the upper respiratory tract for primary vaccinations or the lower respiratory airways for secondary, booster vaccinations; (4) be easy to disperse into their primary particle size; (5) be non-hygroscopic to prevent hygroscopic growth of the vaccine virus-loaded particles in the airways during respiration (Morrow, 1986); and (6) be non-toxic for man, animals and the environment. In previous research Newcastle disease virus (NDV) powder vaccines based on mannitol and bovine serum albumin (BSA), which approximated to the requirements mentioned above, were prepared in a onestep spray-drying process (Corbanie et al, 2007;Huyge et al, 2012). A preliminary proof of principle experiment showed that the powder vaccine formulations induced high haemagglutination inhibiting (HI) antibody titres in 4-weekold broilers (Corbanie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%